Minimally Invasive Percutaneous Tube Cystostomy using Pigtail Catheter for the Surgical Management of Urolithiaisis in Bucks - S M, Venkatesh; D R, Manjunatha; N, Nagaraju; Balappanavar, B R; N M, Rajashailesh; A J, Shankaregowda; D, Ramesh; M J, Kanteshkumar; Dongre, Nakul A; R, Swaroop (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Urolithiasis is a frequent disease of ruminants caused by the formation of stones in the kidneys and urinary tract with a subsequent blockage to urine outflow leading to uraemia and death. Six male goats showing symptoms of urolithiais were subjected to physical, clinical, haematobiochemical, radiological and ultrasonographic examination. Haematobiochemical examination on day of presentation showed elevated Hb, TLC, BUN, creatinine, hyponatreamia and hypochloreamia. Radiological examination showed distended urinary bladder, and ultrsonographic assessment revealed distended bladder with hyperechoic sludge and granular like particles in four animals and cystolith with acoustic shadowing in two cases. The goats were administered with spinal anaesthesia at lumbosacal region, inj. butorphanol @ 0.2 mg/kg b.wt. I/V and inj. Diazepam @ 0.3 mg/kg b.wt. I/V for sedation. Minimally Invasive Percutaneous Tube Cystostomy (MIPCTC) was done using 14-18 FG Pigtail catheter following aseptic preparation of the surgical site and the catheter were anchored to abdominal wall using 2-3 stay sutures with polyamide. Perioperatively animals were administered with inj. Tramadol @ 2 mg/kg b.wt. and Ceftriaxone @ 10 mg/kg b.wt., intravenously. Post-operatively heamato-biochemical parameters were recorded on day 1, 5, 10 and 15. Ammonium chloride was given per orally for one month @ 200 mg/kg b.wt. as urinary acidifier. Catheter was blocked intermittently to check the urethral patency. All goats showed uneventful recovery, with the success rate of 100% through MIPCTC in animals with intact and distended urinary bladder.